Veinte años después de la publicación del Informe Final de la Comisión de la Verdad y Reconciliación - Villasante Cervello, Mariella (Pontificia Universidad Católica del Perú, 2024)
There has been no concern on the part of the State to educate young people about what Peru experienced between 1980 and 2000, nor has the work of the CVR been sufficiently valued. Since Fujimori’s time, a parallel history was created, and all the crimes perpetrated by the State, especially those whose main leader was Fujimori, remained unnoticed, hidden, despite the fact of being State crimes. But at least in the judicial field progress was made and it was one of the causes for Fujimori’s extradition and conviction. Furthermore, the forced disappearances were hidden, as far as the military leaders were concerned, by the State itself, because when the Ministry of Defense was asked for the names of the soldiers who had acted under pseudonyms, the CVR did not receive any names. Likewise, there is the Reparations Council for victims, created in 2006; Financial reparations have been made to individual and collective victims due to social pressure during the time of President García. But in moral reparations, education, and health, not much progress has been made. Those who have followed the IF better are the populations where there have been victims, they are the ones who best remember and vindicate the work of the CVR. Finally, where the most progress has been made is in the field of the arts, through films, theater, and literature.

No ha habido por parte del Estado la preocupación por educar a los jóvenes respecto de aquello que vivió el Perú entre 1980 y 2000, ni se ha valorado lo suficiente la labor de la CVR. A partir de la época de Fujimori se fue creando una historia paralela, y todos los crímenes perpetrados por el Estado, sobre todo aquellos que tuvieron como dirigente principal a Fujimori, quedaron desapercibidos, escondidos; y eran crímenes de Estado. Pero al menos en el terreno judicial sí se avanzó y fue una de las causales para la extradición de Fujimori y su condena. Además, las desapariciones forzadas fueron ocultadas, en lo que toca a los jefes militares, por el propio Estado, porque cuando se pedían al Ministerio de Defensa los nombres de los militares que habían actuado con seudónimos, la CVR no recibió ningún nombre. Asimismo, existe el Consejo de Reparaciones de las víctimas, creado en 2006; se ha reparado financieramente a víctimas individuales y colectivas por la presión social en la época del presidente García. Pero en las reparaciones morales y de la educación, de la salud, no se ha avanzado mucho. Los que han seguido mejor el IF son las poblaciones donde ha habido víctimas, son ellas las que recuerdan y reivindican mejor el trabajo de la CVR. Finalmente, donde se ha avanzado más es en el terreno de las artes, a través de películas, de teatro, de literatura.
Keywords: IF of the CVR; Crimes of SL and crimes of the State; Justice; Reparations Council; IF de la CVR; Crímenes de SL y crímenes del Estado; Justicia; Consejo de Reparaciones; https://purl.org/pe-repo/ocde/ford#6.00.00